Application of non-invasive prenatal testing to 91,280 spontaneous pregnancies and 3477 pregnancies conceived by in vitro fertilization - Rong Wei; Jingran Li; Yuanyuan Xia; Chaohong Wang; Xinran Lu; Yuqin Fang; Jiansheng Zhu (Molecular Cytogenetics, 2023)
Abstract Background Many clinical studies based on spontaneous pregnancies (SPs) have demonstrated the superiority of non-invasive prenatal testing (NIPT), and the question of whether this technology is suitable for offspring conceived by assisted reproductive technology has attracted attention. This study aimed to evaluate the application value of NIPT in screening for trisomy (T)21, T18, T13 and sex chromosome aneuploidy (SCA) in pregnant women who conceived by in vitro fertilization (IVF). Results In total, there were 804 high-risk cases [0.88% (804/91280), singleton = 795, twin = 9] in the SP group. Among the 558 invasive prenatal diagnosis (IPD) cases (singleton = 556, twin = 2), 343 (singleton = 342, twin = 1) were true positive, including 213 cases of T21, 28 of T18, 5 of T13 and 97 (singleton = 96, twin = 1) of SCA. The positive predictive values (PPVs) of T21, T18, T13, SCA and T21/T18/T13 combined in singleton pregnancy were 89.12% (213/239), 51.85% (28/54), 21.74% (5/23), 40.00% (96/240), and 77.85% (246/316), respectively, and the PPV of SCA in twin pregnancy was 100.00%. In the IVF group, IPD was performed in 19 (singleton = 16, twin = 3) of the 27 high-risk cases [0.78% (27/3477), singleton = 16, twin = 3], of which 9 (singleton = 8, twin = 1) were true positive, including 5 cases (singleton = 4, twin = 1) of T21 and 4 of SCA. The PPVs of singleton T21, SCA and T21/T18/T13 combined were 66.67% (4/6), 50.00% (4/8) and 57.14% (4/7), respectively, and the PPV of twin T21 was 100.00% (1/1). There were no significant differences in PPV among T21, SCA and T21/T18/T13 combined in singletons between the groups (89.12% vs. 66.67%, p = 0.09; 40.00% vs. 50.00%, p = 0.57; 77.85% vs. 57.14%, p = 0.20). The sensitivity and specificity were higher for singleton and twin pregnancies in the two groups. Based on follow-up results, 1 case of false negative T21 was found in the singleton SP group. Additionally, the mean foetal fraction (FF) of the IVF group was lower than that of the SP group (11.23% vs. 10.51%, p < 0.05). Conclusion NIPT has high sensitivity and specificity in screening chromosomal aneuploidies in both IVF pregnancy and spontaneous pregnancy, so it is an ideal screening method for IVF pregnancy.